Apontamentos de um curso de extensão: formação de gestores em sexualidade e educação sexual - Leão, Andreza Marques de Castro [UNESP]; Silva, Carla Bessa da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sexuality has been getting space to be a matter of discussion. School, while an important social instance, is one of the locus in which this subject is present, being summoned to bring this issue up, even because it has been becoming evident in a daily basis in the students´ questions, in their curiosities, games, among others. Considering that the scientific Literature claims that the professionals in education do not carry a specific and accurate formation to deal with this issue, which brings to a lack of instruments on how to start on a work directed to this theme, the present study has been designed, indeed, an extension project, focused on forming managers of a São Paulo state county, so they could be able to, from this course on, enclose this subject, possessing the correct preparation to know how to implement the sexual education work.

A sexualidade tem angariado espaço para ser problematizada. A escola, enquanto importante instância social é um dos lócus no qual este tema está presente, sendo conclamada a abordar este assunto, seja porque ele surge cotidianamente nas dúvidas dos alunos, nas suas curiosidades, brincadeiras, entre outros. Considerando que a literatura científica afirma que os profissionais da educação não apresentam uma formação específica para tratar este tema, o que acarreta falta de instrumentalização de como iniciar um trabalho direcionado a esta temática, delineou-se o presente estudo, de fato, um projeto de extensão, voltado a formar gestores de um município do interior do Estado de São Paulo, de maneira que pudessem, a partir deste curso, abarcar este tema, tendo o devido preparo para saber como implementar o trabalho de educação sexual.
Keywords: Managers; Sexual education; Formation; Gestores; Educação sexual; Formação